Research on the Elbow Passing Ability of Crawler Pipeline Inspection and Repair Robots - Li Jian; Yan Hongwei; Liu Yi; Kou Ziming; Zhang Dengxiao (Jixie chuandong)
The pipeline plays an important role in the transportation of energy, and its safe, reasonable and stable operation is of great significance. This study takes DN250-350 mm oil and gas pipelines as the main application scenario, and plans to design a crawler-type pipeline inspection and repair robots that use a screw nut reducing mechanism to achieve diameter reduction to achieve self-adaptive purposes. The crawler-type pipeline inspection and repair robot can be divided into a drive unit, a detection unit, a connection unit and an isolation repair unit. When the length of the constituent unit of the robot is less than 452.88 mm, it can pass through the elbow from the analysis of geometric constraints. The speed equation of the robot can be obtained by analyzing the motion state of the robot during the running process by the coordinate transformation method. The crawler robot moves more smoothly when passing through the bend with the 3-track differential characteristic. By means of simulation analysis and experimental verification, the passing ability of the elbow is verified. The research on the passing ability of the crawler-type pipeline inspection and repair robot can provide some references for the stable inspection, emergency security and treatment of oil and gas pipelines.